PENGARUH PEMBERIAN DIET TINGGI KALSIUM TERHADAP PENURUNAN BERAT BADAN PADA Rattus novergicus galur wistar - Widodo, Widodo; Tanu K, I Nengah; Waliyo, Edy (Fakultas Kedokteran Universitas Brawijaya, 2006)
ABSTRACT Calcium diet has an important role in energy metabolism regulation especially intracellular Ca2+ which is the key tarrange the metabolism of adiposity fat and triasilgliserol save. When intracellular Ca2+ increase it makes the stimulatioof gen lipogenic and lipogenesis also forcing of lipolysis and finally increasing the fat fitting and increasing adiposity. Thlow level of calcium absorbtion increases the production of calsitirol which could stimulate adiposity Ca2+ influx and thconcequance is the increase of adiposity, so it needs high calcium diet to delay lipogenesis increase of lipolysis, lipioksidaxion, to reduce fat adiposity and weight. The research used pretest – postest control group design. Trial animawere male rat of Rattus novergicus strain wistar. The research consisted of 2 phases. The first phase was increasing thrat weight by giving normal diet with calcium of 0,4% for all kinds of rats for 4 weeks. The second phase by giving calciumdiet with different doses that is group A as control group (0,4% Ca as normal diet), group B 0,8% Ca (Ca as normal diet +0,4% Ca as CaCO3), group C 1,2% Ca (Ca as normal diet + 0,8% Ca as CaCO3) and group D 1,6% Ca(Ca as normadiet + 1,2% Ca as CaCO3) for 4 weeks. To find out the difference of calcium diet it used statistical test Oneway Anova